Mechanistic insights into the peroxisome proliferator-activated receptor alpha as a transcriptional suppressor - Yagai, Tomoki; Nakamura, Takahisa (Frontiers in Medicine, 2022)
Non-alcoholic fatty liver disease (NAFLD) is one of the most prevalent hepatic disorders that 20-30% of the world population suffers from. The feature of NAFLD is excess lipid accumulation in the liver, exacerbating multiple metabolic syndromes such as hyperlipidemia, hypercholesterolemia, hypertension, and type 2 diabetes. Approximately 20-30% of NAFLD cases progress to more severe chronic hepatitis, known as non-alcoholic steatohepatitis (NASH), showing deterioration of hepatic functions and liver fibrosis followed by cirrhosis and cancer. Previous studies uncovered that several metabolic regulators had roles in disease progression as key factors. Peroxisome proliferator-activated receptor alpha (PPARα) has been identified as one of the main players in hepatic lipid homeostasis. PPARα is abundantly expressed in hepatocytes, and is a ligand-dependent nuclear receptor belonging to the NR1C nuclear receptor subfamily, orchestrating lipid/glucose metabolism, inflammation, cell proliferation, and carcinogenesis. PPARα agonists are expected to be novel prescription drugs for NASH treatment, and some of them (e.g., Lanifibranor) are currently under clinical trials. These potential novel drugs are developed based on the knowledge of PPARα-activating target genes related to NAFLD and NASH. Intriguingly, PPARα is known to suppress the expression of subsets of target genes under agonist treatment; however, the mechanisms of PPARα-mediated gene suppression and functions of these genes are not well understood. In this review, we summarize and discuss the mechanisms of target gene repression by PPARα and the roles of repressed target genes on hepatic lipid metabolism, fibrosis and carcinogenesis related to NALFD and NASH, and provide future perspectives for PPARα pharmaceutical potentials.